137k views
5 votes
The function f and g are such that f(x) =2x + 5 /(x -4) and g(x) = 2x – 3 Calculate the value of(i) g(4) (ii) fg(2) (iii) gˉ¹(7)​

User Hasya
by
5.0k points

1 Answer

0 votes

Answer:

g(4) = 5, fg(2) = 7/-3, gˉ¹(7)​ = 2

Explanation:

i.) g(4)= 2(4) -3

g(4) = 8 -3

g(4) = 5

ii.) fg(2)

g(2) = 2(2)-3

g(2)= 4-3

g(2) = 1

fg(2) = 2(1)+5/1-4

fg(2) = 7/-3

iii.) g(x) = 2x -3

g(y) = 2y -3

x = 2y -3

x-3 = 2y

y= (x-3)/2

gˉ¹(7)​ = ((7)-3)/2

gˉ¹(7)​ = 4/2

gˉ¹(7)​ = 2

User Jeff Silverman
by
5.7k points